BMI is inversely correlated to the risk of mortality in patients with type 2 diabetes hospitalized for acute heart failure: Findings from the Gulf aCute heArt failuRE (Gulf-CARE) registry. (15th August 2017) - Abi Khalil, Charbel; Sulaiman, Kadhim; Singh, Rajvir; Jayyousi, Amin; Asaad, Nidal; AlHabib, Khalid F; Alsheikh-Ali, Alawi; Al-Jarallah, Mohammed; Bulbanat, Bassam; AlMahmeed, Wael; Dargham, Soha; Ridha, Mustafa; et al.
Abstract: Background: A U-shaped relationship has been reported between BMI and cardiovascular events among patients with acute heart failure (AHF). We hypothesized that an obesity paradox also governs the relationship between BMI and mortality in patients with type 2 diabetes (T2D) and AHF. Methods: We studied 3-month and 12-month mortality in patients with T2D hospitalized for AHF according to 5 BMI categories: Underweight (< 20 kg/m 2 ), normal weight (referent group, 20–24.9 kg/m 2 ), overweight, (25–29.9 kg/m 2 ), obese (30–34.9 kg/m 2 ) and severely obese (≥ 35 kg/m 2 ), in the Gulf aCute heArt failuRe rEgistry (GULF-CARE). Results: Among the 5005 participants in this cohort, 2492 (49.8%) had T2D. Underweight patients had a higher 3-month and 12-month mortality risk (OR 2.04, 95% CI [1.02–4.08]; OR 2.44, 95% CI [1.35–4.3]; respectively), compared to normal weight. Severe obesity was associated with a lower 3-month and 12-month mortality risk (OR 0.53, 95% CI [0.34–0.83]; OR 0.58, 95% CI [0.42–0.81]; respectively). After adjustment for several risk variables in 2 different models, the primary outcome was still significantly increased in underweight patients, and decreased in severely obese patients, at 3 months and 12 months. Further, the odds of mortality decreases with increasing BMI by 0.38 at 3 months and at 0.45 at 12 months in a near-linear shape ( p  = 0.007; p  = 0.037; respectively). Conclusions: In this cohort of patients with AHF, BMI was inversely correlated to the risk of mortality in patients with T2D. Moreover, severe obesity was associated with less mortality risk.